Atletas da modalidade esportiva do voleibol - relações entre as lesões nos membros superiores e o desempenho nas ocupações: uma revisão sistemática com síntese narrativa - Antão, Rosangela Aline (Universidade Federal de São Carlos, 2022)
The daily life of volleyball athletes is filled with an exorbitant amount of specific activities directly derived from their main occupational role (athlete). Since it is a practice that involves the constant use of the upper limbs, there is the possibility of injuries in this region of the body and, therefore, a demand for occupational therapy with performance in Hand Therapy and Upper Limb Rehabilitation. When working with this population according to the Model of Human Occupation, it is assumed that the engagement in occupations has a personal motivation and requires a set of performance skills, and that an injury can directly compromise the relationship between the subject and his occupation. The intent of this paper was to conduct a systematic review of the literature to investigate the most common upper limb injuries in volleyball practice in order to produce a narrative synthesis of the results and correlate them with Occupational Therapy in Sports, Hand Therapy, and the Model of Human Occupation. To this end, a systematic literature review was conducted in the CAPES Periodicals database over the last 10 years and a two-stage analysis of the results, which allowed for synthesis and discussion: 1) Organization of the studies into logical categories by means of two tables (bibliometric information and PICOT acronym); 2) From the analysis of the categories and in comparison with the objectives of the work, definition of two guiding themes of the narrative synthesis ("Injuries and performance in the practice of volleyball" and "The performance of occupational therapy in sport from the Model of Human Occupation"). Thus, it was possible to observe a gap of two years between the publications found, as well as between 2001-2014 and 2016-2021. Finally, the narrative synthesis allowed for the understanding that repetitive movements above head height, the intensity and duration of training, the long duration of the athletes' careers, and the performance of exercises to increase strength, may cause impacts on the participation and occupational engagement of these subjects. In this context, therefore, Occupational Therapy in its work within Hand Therapy and Upper Limb Rehabilitation, based on the assumptions of the Model of Human Occupation, has the possibility of working on the goals and objectives of interventions focused on meaningful occupations and activities for these athletes, promoting and enabling engagement in meaningful occupations.
Athletes in the sport of volleyball - relationships between upper limb injuries and occupational performance: a systematic review with narrative synthesis
Keywords: Voleibol; Lesão; Ocupações; Extremidade Superior; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL